Effectiveness of cognitive behavioral therapy integrated with systematic desensitization, cognitive behavioral therapy combined with eye movement desensitization and reprocessing therapy, and cognitive behavioral therapy combined with virtual reality exposure therapy methods in the treatment of flight anxiety: a randomized trial - Triscari MT; Faraci P; Catalisano D; D’Angelo V; Urso V (Neuropsychiatric Disease and Treatment, 2015)
Maria Teresa Triscari,1 Palmira Faraci,2 Dario Catalisano,3 Valerio D’Angelo,1 Viviana Urso1 1Laboratory for Psychosomatic Disorders, Local Health Trust, Palermo, Italy; 2Faculty of Human and Social Sciences, University of Enna “Kore”, Enna, Italy; 3Italian Flight Safety Committee, Aeroporto di Fiumicino, Fiumicino (RM), Italy Abstract: The purpose of the research was to compare the effectiveness of the following treatment methods for fear of flying: cognitive behavioral therapy (CBT) integrated with systematic desensitization, CBT combined with eye movement desensitization and reprocessing therapy, and CBT combined with virtual reality exposure therapy. Overall, our findings have proven the efficacy of all interventions in reducing fear of flying in a pre- to post-treatment comparison. All groups showed a decrease in flight anxiety, suggesting the efficiency of all three treatments in reducing self-report measures of fear of flying. In particular, our results indicated significant improvements for the treated patients using all the treatment programs, as shown not only by test scores but also by participation in the post-treatment flight. Nevertheless, outcome measures maintained a significant effect at a 1-year follow-up. In conclusion, combining CBT with both the application of eye movement desensitization and reprocessing treatment and the virtual stimuli used to expose patients with aerophobia seemed as efficient as traditional cognitive behavioral treatments integrated with systematic desensitization. Keywords: flight anxiety, fear of flying, aerophobia, cognitive behavioral therapy, EMDR, VRET